Comparative Analysis Of Conjunctions In Uzbekistan And English - Uktamova, Mokhigul; Vahobjonova, Muniraxon (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article provides a comparative analysis of conjunctions in Uzbek and English. The study examines the types, use, and similarities and differences of conjunctions between the two languages. Conjunctions play an important role in syntax and sentence structure, but there are differences in meaning and usage. In addition, their role in syntax, their function in sentence structure, and similarities and differences between the two languages ​​are examined. The results show that conjunctions are important in the grammatical rules of both languages, but their tone of use and adaptation to the context differ. The study is aimed at students, language It is useful for learners and linguists, and provides practical advice on the correct and effective use of conjunctions.